Taxonomi’s Bloom and Level In Reading Comprehension Test - Erlidawati; Aulia, Shirma (ABANNA: Journal Of Contemporary Islamic Education, 2023)
The capacity to comprehend the factual information provided in a text passage after reading it is known as reading comprehension. Reading comprehension is divided into four categories: literal, interpretive, evaluative, and creative. The goals of the study were to identify the levels and characteristics that teachers employed when administering reading comprehension tests. The researcher employed a descriptive qualitative method to collect the data. Interviews and documentation sheets are the tools used to collect data. This study's findings are qualities and levels that teachers use in their reading comprehension assessments. First, questions are tested in a mixed category, which indicates a medium's quality even though more questions fall into the high category than the low category. Twelve products that revealed the dominating. Out of all the reading comprehension test questions in the classification, the literal level (which appears five times) and the form C1 (remember) comprise the twelve items that determined the dominant cognitive thinking and levels of the category. The second question, which had three appearances throughout the test overall, was in the format of C2 (comprehend), C4 (analyze), interpretive, and critical level. The third, the C5 (evaluate) question form and creative level, appeared once during the entire test.